Kinetics of oil palm empty fruit bunch fiber pyrolysis - Bashar Abdullahi Hadi; Abdullahi Muhammad Sokoto; Aminu Bayawa Muhammad; Yahaya Alhassan; Chika Muhammad (Academia Green Energy)
This work explores the kinetics of producing sustainable hydrocarbons from oil palm empty fruit bunch (EFB) fiber. A one-step global model was used to study the dynamics of the EFB fiber using the Coats and Redfern (CR) model-fitting kinetics technique. The non-isothermal iso-conversional methods of Friedman (FD), Kissinger-Akahira-Sunose (KAS), and Flynn-Wall-Ozawa (FWO) were also examined. Different heating rates (5, 10, and 15°C/min) were used for the thermogravimetric analysis. The best-fitting equations were used to fit the CR model and determine the thermodynamic parameters. The reaction is diffusion regulated by nucleation and nuclei growth models, according to the Zhuravlev-Lasokin-Tempelman model, which produced the highest regression value and the best acceptable fit. Out of all the model-free methods, FD showed the greatest apparent activation energy levels when compared to the iso-conversion methods KAS and FWO. The changes in entropy (−123 to 135), Gibbs free energy (150–156 kJ/mol), and activation enthalpy (63–71 kJ/mol) were computed using the best-fitting model. The maximum apparent activation energy was found using the FD iso-conversion technique.